Younger Age of Presentation and Extraosseous Tumour in IgD Myelomatosis. Issue 5641 (15th February 1969) - Hobbs, J. R.; Corbett, A. A.
Abstract : A study of 14 personal patients and 16 others in the literature shows that (1) IgD myelomatosis often presents at a significantly younger age than other forms of myelomatosis, and (2) during life extraosseous tumour can be detected in about two-thirds of these patients. The IgD form represents 1·5% of myelomatosis and shows an increased incidence of osteolytic lesions, hypercalcaemia, and renal failure, together with heavy Bence Jones proteinuria (90% type L). Like only Bence Jones myelomatosis, the IgD form seems to behave clinically in a more vicious manner.